ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI JAGUNG DI KECAMATAN ULUBONGKA KABUPATEN TOJO UNA-UNA - Jafar, Moh. Ikram; Anwar, Chairil; Damayanti, Lien (Katalogis, 2020)
The objective of this research is to find out income of corn farmers and income contribution of corn farmers to total income household, feasibility level of corn farmers, well-being level of corn farmers household in Ulubongka district of Tojo Una-una regency. The results of the research show that (1) The average income obtained by corn farmers in Bongka Makmur village is IDR. 11.915.368/planting season. The average income of corn farmers received by farmers in Bongka Makmur village is IDR. 2.978.842 per month. (2) Income contribution of corn farmers is 69,10%. This matter shows that corn farmers contributes the most income of farmer households. (3) Feasibility of corn farmers in Bongka Makmur village by using financial analysis, namely Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR) and Benefit Cost Ratio (B/C Ratio) show that corn farmers in Bongka Makmur village is worth trying. (4) The well-being of corn farmers household in Bongka Makmur village is in sufficient based on the criteria of Sajogyo (1997) by using the poverty rate.